Differences in Molecular Pathologic Characteristics of Pancreatic Adenocarcinoma between Egyptian and Moroccan Patients - Robinson, Sara (Middle East J Cancer, 2010)
INTRODUCTION: Pancreatic cancer has not been well studied, especially in developing countries. MATERIALS AND METHODS: We studied the variations in genetic mutations in pancreatic adenocarcinoma between Moroccan and Egyptian populations. The molecular pathology of 30 tumors from a large hospital in Casablanca, Morocco were examined and compared with the findings of 44 tumors from the Gharbiah Governate in Egypt. K-ras mutations in codons12 and 13 in addition to p53 mutations in exons 5–8 were evaluated. RESULTS: Overall, differences in the rates of K-ras mutations were not statistically significant (48.00 and 34.09%, respectively); however differences in rates of p53 mutations were statistically significant with p53 mutations more common in Moroccan tumors than in Egyptian tumors (46.67 and 16.28%, respectively). GT mutations of the K-ras gene were most commonly seen Egyptian tumors, whereas G → A mutations were the most common type of mutations in Moroccan tumors. Logistic regression analysis showed that a p53 mutation in any exon as well as a p53 mutation in exon 5 predicted the country of residence and those mutations occurred more frequently in Moroccan patients. CONCLUSION: Our study shows that differences exist within the Arab population in the molecular pathology of both the K-ras and p53 genes. Further studies are necessary to clarify the differences in molecular pathways of pancreatic cancer in the Middle East and to investigate the role of environmental and/or genetic factors related to those pathways.